2023
DOI: 10.2490/prm.20230010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Activities of Daily Living in Intensive Care Unit Survivors: A Propensity Score Matching Analysis

Abstract: Objectives: Increased long-term impairment is common among intensive care unit (ICU) survivors. However, predictors of activities of daily living (ADL) in ICU survivors are poorly understood. We aimed to focus on the trajectory of physical function and explore the clinical variables that affect ADL at hospital discharge. Methods: We enrolled 411 patients admitted to the ICU from April 2018 to October 2020. Physical function was evaluated at ICU admission, ICU discharge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In our study, ROC curve analysis was used to demonstrate the predictive value of MAC, and TSF as regards the mortality in ICU patients and hand grip strength as regards the mortality in ICU patients. This was in agreement with a recent study by Tsuyoshi Matsumoto, et al [19] who reported that, ROC analysis determined 27cm as the cut-off value of the relative change in the MAC as a predictor of mortality in ICU individuals with a p-value <0.001 sensitivity of 77.8%, a specificity of 55.6%, and the area under the curve (AUC) was 0.681.…”
Section: Aki: Acute Kidney Injurysupporting
confidence: 92%
“…In our study, ROC curve analysis was used to demonstrate the predictive value of MAC, and TSF as regards the mortality in ICU patients and hand grip strength as regards the mortality in ICU patients. This was in agreement with a recent study by Tsuyoshi Matsumoto, et al [19] who reported that, ROC analysis determined 27cm as the cut-off value of the relative change in the MAC as a predictor of mortality in ICU individuals with a p-value <0.001 sensitivity of 77.8%, a specificity of 55.6%, and the area under the curve (AUC) was 0.681.…”
Section: Aki: Acute Kidney Injurysupporting
confidence: 92%